2004
DOI: 10.1111/j.1365-2966.2004.08340.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of 6.7-GHz methanol masers

Abstract: A sample of 54 6.7-GHz methanol masers was monitored using the Hartebeesthoek 26-m telescope during the period 1999 January -2003 March. The observations were taken at 1-2 week intervals, with daily observations when possible if a source was seen to be varying rapidly. It was found that the majority of the sources display a significant level of variability. The timerange of variations range from a few days up to several years. The types of behaviour observed included non-varying, monotonic increases or decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
228
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(251 citation statements)
references
References 32 publications
(79 reference statements)
18
228
4
Order By: Relevance
“…This pair of methanol masers has been found to show variability in both sites (Caswell et al 1995). Goedhart et al (2004) monitored these methanol masers over more than four years and found no periodicities on these timescales. The water maser associated with 345.003-0.223 was also detected by Breen et al (2010a) in 2003 to have a peak flux density of 3.0 Jy, in 2004 at 3.7 Jy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pair of methanol masers has been found to show variability in both sites (Caswell et al 1995). Goedhart et al (2004) monitored these methanol masers over more than four years and found no periodicities on these timescales. The water maser associated with 345.003-0.223 was also detected by Breen et al (2010a) in 2003 to have a peak flux density of 3.0 Jy, in 2004 at 3.7 Jy.…”
Section: Resultsmentioning
confidence: 99%
“…Det Caswell et al (1995) and monitored by Goedhart et al (2004), and no periodicities in the variability were observed. The associated water maser emission is also quite variable, in 2003 it had a peak flux density of 7 Jy, in 2004 14 Jy (Breen et al 2010a) and in our 2011 observations 80.2 Jy.…”
Section: Mmb Targetmentioning
confidence: 99%
“…First, in the point of view of the ratio of the peak flux density in the flare and quiescence, the flares at the component G in G 014.23 can be compared to a spectral component of V lsr = −5.88 km s −1 in G 351.42+00.64 (NGC6334 F: Goedhart et al 2004) and those of V lsr = −1.32 and −0.55 km s −1 in Cepheus A (Szymczak et al 2014). The spectral components in both sources showed ratios of the peak flux density in the flare of 170 and 240 in comparison with the quiescent phase.…”
Section: Comparison With Other Flaring Sourcesmentioning
confidence: 99%
“…So far, the periodic flux variability of the methanol masers has been detected in 20 sources (including quasi-periodic ones). Their periods range from 29.5 to 668 days (Goedhart et al 2004Araya et al 2010;Szymczak et al 2011Szymczak et al , 2014Szymczak et al , 2015Szymczak et al , 2016Fujisawa et al 2014a;Maswanganye et al 2015Maswanganye et al , 2016. Patterns of the variability have been classified into two categories: the sinusoidal one, and the intermittent one with a quiescent phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation